2021
DOI: 10.1093/jla/laaa006
|View full text |Cite
|
Sign up to set email alerts
|

Shining a Light on Dark Patterns

Abstract: Dark patterns are user interfaces whose designers knowingly confuse users, make it difficult for users to express their actual preferences, or manipulate users into taking certain actions. They typically exploit cognitive biases and prompt online consumers to purchase goods and services that they do not want or to reveal personal information they would prefer not to disclose. This article provides the first public evidence of the power of dark patterns. It discusses the results of the authors’ two large-scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
109
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(114 citation statements)
references
References 13 publications
0
109
0
5
Order By: Relevance
“…One of such manipulative UI designs is dark patterns-"tricks used in websites and apps that make you do things that you didn't mean to, like buying or signing up for something" [14]. Here, consumers cannot follow their preferences and desires and become subject to exploitation [6]. Dark patterns are heavily rooted in psychology and behavioral sciences findings, applying knowledge about humans' reliance on heuristics and biases into the digital space.…”
Section: Information and Ui Designmentioning
confidence: 99%
See 3 more Smart Citations
“…One of such manipulative UI designs is dark patterns-"tricks used in websites and apps that make you do things that you didn't mean to, like buying or signing up for something" [14]. Here, consumers cannot follow their preferences and desires and become subject to exploitation [6]. Dark patterns are heavily rooted in psychology and behavioral sciences findings, applying knowledge about humans' reliance on heuristics and biases into the digital space.…”
Section: Information and Ui Designmentioning
confidence: 99%
“…One example of such abuse is dark patterns. To tackle the dark patterns and clarify their effects, researchers attempted to categorize them [7,9,10,6]. For instance, [6] summarized the existing categorizations as the main eight categories: nagging, social proof, obstruction, sneaking, interface interference, forced action, scarcity, and urgency.…”
Section: Digital Design and Dark Patternsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the visual aspect, one can notice a second strategy in the above example, namely that the accept option is framed positively by stating "Yes, I'm happy", while the more neutral option leading to the privacy customization page is framed in a neutral tone as well. Recent work by Utz et al [11] and Luguri and Strahilevitz [6] showed that such design choices highly influence the decision making of users, and hence, one can assume that designers include these patterns deliberately into their work. Providing such insights is an important task, and we highly appreciate the work that is done to establish best practices and guidelines for designers to follow, such that they can avoid these malicious patterns.…”
Section: Introductionmentioning
confidence: 99%